Integrasi Seni Japin Carita dalam Pembelajaran Seni Transformatif: Upaya Revitalisasi Identitas Budaya Lokal di Sekolah Dasar - Bagus Aulia Iskandar; Aldy Ferdiyansyah (Universitas Nusa Cendana, 2026)
This study aims to explore the integration strategies of Japin Carita performance art as a transformative arts education instrument capable of maintaining and developing Banjar cultural identity in elementary school students. Amidst the accelerating threat of local cultural extinction due to digital globalization, Japin Carita offers a vital medium for value revitalization through its unique blend of dance, music, and educational narratives. This research employs a qualitative literature review method, systematically analyzing various academic sources, cultural documents, and pedagogical frameworks related to the philosophical values of Japin Carita and educational practices that support cultural sustainability. The results demonstrate that Japin Carita possesses high urgency to be reintegrated into the school ecosystem, not merely as a decorative subject, but as a core component of character building. The study identifies that the Projek Penguatan Profil Pelajar Pancasila (P5) work exhibitions serve as a strategic platform for students to actively engage in the creative process, from scriptwriting to public performance. This active participation fosters a sense of pride and ownership over their ancestral heritage. Furthermore, the integration of local wisdom, such as the Gawi Sabumi philosophy, into the school curriculum helps bridge the gap between traditional values and modern competencies. The conclusion emphasizes that the survival of local Banjar culture depends heavily on the systemic efforts of schools to transform traditional arts into a living, dynamic practice that is relevant to students' contemporary lives, rather than treating them as stagnant artifacts of the past. This approach ensures that cultural identity remains a resilient foundation for future generations.